2018
DOI: 10.3758/s13423-018-1438-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-level orientation information for social evaluation in face images

Abstract: Observers make a range of social evaluations based on facial appearance, including judgments of trustworthiness, warmth, competence, and other aspects of personality. What visual information do people use to make these judgments? While links have been made between perceived social characteristics and other high-level properties of facial appearance (e.g., attractiveness, masculinity), there has been comparatively little effort to link social evaluations to low-level visual features, like spatial frequency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Faces are an important source of social information and the ability to recognize, interpret, and respond appropriately to human faces is paramount to social functioning . These skills, as well as their neural mechanisms, are an important part of development .…”
Section: Introductionmentioning
confidence: 99%
“…Faces are an important source of social information and the ability to recognize, interpret, and respond appropriately to human faces is paramount to social functioning . These skills, as well as their neural mechanisms, are an important part of development .…”
Section: Introductionmentioning
confidence: 99%
“…The general mechanism underlying serial dependence of face perception offers new evidence for a better understanding of social evaluation in face processing. Previous studies have shown that people make facial judgments in social context based on high-level properties of facial appearance (e.g., masculinity), as well as a multiple-channel representation of facial appearance at early age of visual processing, suggesting a task-specific mechanism in social trait evaluation ( Balas & Verdugo, 2018 ). For example, evaluation of trustworthiness depends critically on horizontal orientation, whereas competence and dominance evaluation do not, which indicates that the visual information used for social evaluation relies on which trait the observers are trying to evaluate ( Balas & Verdugo, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These social judgments play a significant role in our daily life: for example, the perceived dominance and trustworthiness of faces can influence leadership decisions ( Ballew & Todorov, 2007 ). As with other perceptual processes, face perception of social characteristics remains relatively stable despite constant changes in visual inputs because of factors including eye movement, shadows, and occlusion; thus researchers called it the invariant aspect of face processing ( Balas & Verdugo, 2018 ; Bruce & Young, 1986 ; Calder & Young, 2005 ). However, the mechanism underlying the temporal stability of facial trait perception remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient face processing play an important role in successful navigation of the social world (see Oruc et al, 2019) and people demonstrate the remarkable ability to process human faces and to identify emotion on faces (Tanaka, 2001). This ability would partly rely on the treatment of low-level information such as orientation and spatial frequencies (Balas and Verdugo, 2018;Oruc et al, 2019). In a visual stimulus, spatial frequency refers to the energy distribution derived from the Fourier transform, and expressed in the number of cycle per degree of visual angle (Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%